Odpowiedzi

Najlepsza Odpowiedź!
2009-11-29T12:44:11+01:00
A)
(x+1)(x²-x+1) = x³-x²+x+x²-x+1=x³+1
b)
(s-2)(s³-s²+s-1) = s⁴-s³+s²-s-2s³+2s²-2s+2 = s⁴-3s³+3s²-3s+2
c)
(ab+1)(a+b+ab+1) = a²b+ab²+a²b²+ab+a+b+ab+1 = a²b+ab²+a²b²+2ab+a+b+1
1 5 1
2009-11-29T12:48:05+01:00
A)(x+1)(x²-x+1)=x³-x²+x+x²-x+1=x³+1
b)(s-2)(s³-s²+s-1)=s⁴-s³+s²-s-2s³+2s²-2s+2=s⁴-3s³+3s²-3s+2
c)(ab+1)(a+b+ab+1)=a²b+ab²+a²b²+ab+a+b+ab+1=a²b+ab²+a²b²+2ab+a+b+1
1 4 1
2009-11-29T12:48:09+01:00
A) (x+1)(x²-x+1)= x³-x²+x+x²-x+1= x³+1
b) (s-2)(s³-s²+s-1)= s⁴-s³+s²-s-2s³+2s²-2s+2 = s⁴-3s³+3s²-3s -2
c) (ab+1)(a+b+ab+1)= a²b+ab²+(ab)²+1+a+b+ab+1=a²b+ab²+(ab)²+a+b+ab+2
1 4 1